2012
DOI: 10.3897/natureconservation.1.2086
|View full text |Cite
|
Sign up to set email alerts
|

Road effects on habitat richness of the Greek Natura 2000 network

Abstract: The road network has both positive and negative ecological effects, and understanding these helps identify environmentally preferable solutions for transportation policy and planning. We investigated the relationship between road density and habitat type richness of Greek protected areas. We used digital vector maps of 214 sites included in the Greek Natura 2000 network. We calculated road density for the terrestrial part of each site and correlated it with habitat type richness. Average road density of protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 74 publications
3
11
0
2
Order By: Relevance
“…Species richness and abundance were instead generally higher in forest older than 120 years, with none or only few traces of wood harvesting. The negative correlation between focal species occurrence and forest roads found in our study is in accordance with recent studies discussing the potential of using road-free areas as conservation targets (Selva et al 2011;Votsi et al 2012). We thus suggest that a low quantity of forest roads can be used as an indicator of still-intact forest landscapes with high conservation values.…”
Section: Scandinavian Journal Of Forest Researchsupporting
confidence: 93%
“…Species richness and abundance were instead generally higher in forest older than 120 years, with none or only few traces of wood harvesting. The negative correlation between focal species occurrence and forest roads found in our study is in accordance with recent studies discussing the potential of using road-free areas as conservation targets (Selva et al 2011;Votsi et al 2012). We thus suggest that a low quantity of forest roads can be used as an indicator of still-intact forest landscapes with high conservation values.…”
Section: Scandinavian Journal Of Forest Researchsupporting
confidence: 93%
“…As shown in Table 8 , only 7 species were recorded in both foreground and background of recordings at location 7 which is closest to the highway compared to 20 species recorded at the location with the highest number which was located further from the road, location 8. This confirms conclusions from other authors that roads have a major impact on wildlife populations (Votsi et al 2012, Goodwin and Shriver 2010). …”
Section: Additional Informationsupporting
confidence: 92%
“…It is noteworthy that these roadless sites are considered in good (n = 2) and excellent (n = 5) conservation status according to our model; which demonstrates their potential as physical corridors, stepping stones or even in preventing further road development. However, despite the significance of roadless areas for biodiversity conservation as relatively less disturbed areas (Strittholt and Dellasala 2001;Crist et al 2005), they are insufficiently known or protected (Votsi et al 2012). As Selva et al (2011) suggest, roadless areas should be identified, mapped and preserved due to their significance in biodiversity conservation initiatives, especially if combined with the N2K network.…”
Section: Discussionmentioning
confidence: 98%